Cognitive impairment and biomarkers of gut microbial translocation in testicular germ cell tumor survivors - Chovanec, Michal; Kalavska, Katarina; Obertova, Jana; Palacka, Patrik; Rejlekova, Katarina; Sycova-Mila, Zuzana; Orszaghova, Zuzana; Lesko, Peter; De Angelis, Valentina; Vasilkova, Lucia; Svetlovska, Daniela; Mladosievicova, Beata; et al. (Frontiers in Oncology, 2023)
Background: Survivors of testicular germ cell tumors (GCT) may suffer from late cognitive impairment. We hypothesized that disruption of intestinal barrier during chemotherapy and/or radiotherapy may be a contributing factor of cognitive dysfunction within the gut-blood-brain axis. Methods: GCT survivors (N = 142) from National Cancer Institute of Slovakia completed the Functional Assessment of Cancer Therapy Cognitive Function questionnaires during their annual follow-up visit at 9-year median (range 4-32). Biomarkers of gut microbial translocation and dysbiosis high mobility group box-1 (HMGB-1), lipopolysaccharide, d-lactate and sCD14 were measured from peripheral blood obtained during the same visit. Each questionnaire score was correlated with biomarkers. Survivors were treated with orchiectomy only (N = 17), cisplatin-based chemotherapy (N = 108), radiotherapy to the retroperitoneum (N = 11) or both (N = 6). Results: GCT survivors with higher sCD14 (above median) had worse cognitive function perceived by others (CogOth domain) (mean ± SEM; 14.6 ± 0.25 vs 15.4 ± 0.25, p = 0.019), lower perceived cognitive abilities (CogPCA domain) (20.0 ± 0.74 vs 23.4 ± 0.73, p = 0.025) and lower overal cognitive function score (109.2 ± 0.74 vs 116.7 ± 1.90, p = 0.021). There were no significant cognitive declines associated with HMGB-1, d-lactate and lipopolysacharide. Survivors treated with ≥ 400mg/m2 vs < 400mg/m2 of cisplatin-based chemotherapy had a higher lipoplysacharide (567.8 g/L ± 42.7 vs 462.9 g/L ± 51.9, (p = 0.03). Conclusions: sCD14 is a marker of monocytic activarion by lipopolysaccharide and may also serve as a promising biomarker of cognitive impairment in long-term cancer survivors. While chemotherapy and radiotherapy-induced intestinal injury may be the underlying mechanism, further research using animal models and larger patient cohorts are needed to explore the pathogenesis of cognitive impairment in GCT survivors within the gut-brain axis.